Adding Multiple Adipokines into the Model do not Improve Weight Gain Prediction by Leptin Levels in Newborns - Treviño Garza, Consuelo; Estrada Zuñiga, Cynthia María; Mancillas Adame, Leonardo Guadalupe; Villarreal Martínez, Laura; Villarreal Pérez, Jesús Zacarías; Rodríguez Balderrama, Isaías; Montes Tapia, Fernando Félix; De la O. Cavazos, Manuel E. (2016)
Objective: Most adipose tissue programming is realized in early life. Also, the postnatal three months, rather than the later phases of infancy, may be more relevant in the development of an adverse cardiometabolic risk profile. The adipokines phenotype, as a predictor of early-life weight gain, has been recently explored in cord blood. To determine whether in addition to leptin levels in cord samples, adiponectin, interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), resistin, plasminogen activator inhibitor-1 (PAI-1), and tumor necrosis factor alpha (TNF-α) levels improve weight gain prediction during the first three months of life.